2003
DOI: 10.4049/jimmunol.171.5.2594
|View full text |Cite
|
Sign up to set email alerts
|

C1 Inhibitor Prevents Endotoxin Shock Via a Direct Interaction with Lipopolysaccharide

Abstract: C1 inhibitor (C1INH) is beneficial in animal models of endotoxemia and sepsis. However, the mechanism(s) of C1INH protection remain(s) ill-defined. In this study, we demonstrated that both active C1INH and reactive center-cleaved, inactive C1INH protected mice from lethal Gram-negative endotoxemia. Both forms of C1INH blocked the LPS-binding protein-dependent binding of Salmonella typhimurium LPS to the murine macrophage cell line, RAW 264.7, and suppressed LPS-induced TNF-α mRNA expression. Inhibition of LPS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
70
2

Year Published

2004
2004
2012
2012

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 69 publications
(77 citation statements)
references
References 42 publications
5
70
2
Order By: Relevance
“…Other data suggest that contact system activation does not play an important role (Feletou et al, 1996). Our data indicated that not only did intact, active C1 inhibitor protect from endotoxin shock, but that treatment with inactive, reactive center cleaved C1 inhibitor also was effective (Liu et al, 2003). Both active and inactive C1 inhibitor also prevented both local and systemic vascular permeability changes in response to endotoxin (Liu et al, 2005b).…”
Section: The Interaction Of C1 Inhibitor With Gram Negative Bacterialsupporting
confidence: 49%
See 4 more Smart Citations
“…Other data suggest that contact system activation does not play an important role (Feletou et al, 1996). Our data indicated that not only did intact, active C1 inhibitor protect from endotoxin shock, but that treatment with inactive, reactive center cleaved C1 inhibitor also was effective (Liu et al, 2003). Both active and inactive C1 inhibitor also prevented both local and systemic vascular permeability changes in response to endotoxin (Liu et al, 2005b).…”
Section: The Interaction Of C1 Inhibitor With Gram Negative Bacterialsupporting
confidence: 49%
“…At least one other protein, MD-2, is associated with CD14 and TLR4 on the cell surface; together, these make up the LPS receptor (da Silva Correia and Ulevitch, 2002;Juan et al, 1995;Stelter et al, 1997;Stelter et al, 1999;Viriyakosol and Kirkland, 1995;Viriyakosol et al, 2000). The binding of C1 inhibitor to LPS (or lipid A) was inhibited by fetal bovine serum, which contains LBP, and by an LBP peptide that includes the binding site for LBP (Liu et al, 2003).…”
Section: The Interaction Of C1 Inhibitor With Gram Negative Bacterialmentioning
confidence: 99%
See 3 more Smart Citations